APLIKASI KERAMIK PADA FUNGSI AROMATHERAPY - Noor Sudiyati (Institut Seni Indonesia Yogyakarta, 2014)
Aromatherapy obtained through combustion of essential oil as the need of health isnow mushrooming in big cities. Essential oil that made of plants has the ability to createrelaxation without causing any side effect. Those herbal such as roses, ginger, jasmine, lemongrass and so on are growing around us and treated with distilled technology.Essential oils can be processed into liquid, stick, and solid, and its use requires aceramic container made of clay. Ceramics is capable to answer the needs of aromatherapyfurnace with such a wide variety of themes, images, expressions and artistic decorations.Frangipani themed ceramic furnace is made for aromatherapy containers used for essentialliquids that are heated with candles burning. This furnace made with incorporated slabtechniques so it has unique character.Key words: Ceramic, Aromatherapy, Herbal theme, aromatherapy, for firing,frangipaniceramic. Kebutuhan akan kesehatan melalui system pembakaran mintak atsiri disebutaromatherapy yang berasal dari herbal marak di kota-kota besar, Minyak atsiri yang terbuatdari tumbuh-tumbuhan ternyata mampu membuat rileksasi, dipakai tanpa meninggalkan efeksamping. Herbal itu banyak tumbuh di sekeliling kita, namun diolah dengan teknologi suling,misalnya saja: bunga kenanga, melati (jasmine), sere, Jahe, mawar dan lain sebagainya.Minyak atsiri (aromatherapy) bisa diolah sehingga dapat berupa cairan, stick, danpadat, dalam penggunaanya memerlukan wadah berupa keramik yang terbuat dari Tanah liat.Keramik mampu menjawab kebutuhan wadah pembakaran atau tungku aromatherapi denganberbagai macam: tema, imaji, ekpresi dan dekorasi yang artistic.Tungku Keramik bertema Kamboja dibuat untuk wadah aromatherapy yang dipakaiuntuk atsiri cairan yang dipanaskan dengan pembakaran lilin. Tungku ini dibuat dengan teknikslab yang digabungkan, menjadi tungku yang berkarakter khas. Kata Kunci: keramik, aromatherapy, herbal, pemanasan, tema kamboja.